POTRET TREN DAN EVALUASI PENEGAKAN HUKUM TINDAK PIDANA PEMILU 2024 - Silalahi, Wilma; Indah Khairunnisa (JIL : Journal of Indonesian Law, 2024)
This study aims to examine the portrait of trends and evaluation of law enforcement of election crimes in 2024. This is because elections are one of the means to realize democracy in Indonesia. As a way to elect representatives who will represent the people in government, the people always look forward to this sacred agenda. Unfortunately, this sacred agenda is still tainted by various criminal acts despite the existence of laws and regulations that prohibit all forms of dirty practices in elections. This can reduce citizens’ enthusiasm and trust in the organization of elections, which in turn can degrade the role of elections as a means of democracy and undermine democratic values. This research is an exploratory study that seeks to explore trends in criminal offenses in the 2024 elections and things that need to be evaluated from law enforcement of criminal offenses in the 2024 elections. The criminal offense trends in the 2024 elections are violations of the neutrality of ASN and state officials, the practice of money politics, and illegal campaign funds. These three cases deviate from the theory of public law protection and the theory of good governance, and injure legal certainty and the principle of openness in the general principles of good governance (AAUPB). There are still shortcomings and obstacles in law enforcement of election crimes in 2024, both in terms of legal structure, legal substance, and legal culture. Therefore, for better elections in the future, the government must take strategic steps in handling election crimes, including through reformulation of the Election Law, special guidance on the integrity of ASN, state officials, and the Gakkumdu Center, as well as improving public welfare and education.